2017
DOI: 10.1159/000462996
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Focus: From Hydration for Performance to Hydration for Health

Abstract: Over the past 10 years, literature on hydration biomarkers has evolved considerably - from (de)hydration assessment towards a more global definition of biomarkers of hydration in daily life. This shift in thinking about hydration markers was largely driven by investigating the differences that existed between otherwise healthy individuals whose habitual, ad-libitum drinking habits differ, and by identifying physiological changes in low-volume drinkers who subsequently increase their water intake. Aside from ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 66 publications
0
36
0
4
Order By: Relevance
“…Increased consumption of water has been associated with a reduced risk of obesity, urinary tract infections, chronic kidney disease, cardiovascular disease, and a reduction in the incidence of hyperglycemia [5][6][7][8][9][10][11]. Despite these benefits, recent cross-sectional surveys have shown that 60% of men and 40% of women do not comply with the EFSA recommendations for daily water intake [12], which may alter the long-term health risk profile in persons who habitually consume low volumes of water on a daily basis [13,14]. Although 40% of women were found to not meet current EFSA standards, they were more than twice as likely to meet the adequate intake standards for daily fluid intake than that of men [12].…”
Section: Introductionmentioning
confidence: 99%
“…Increased consumption of water has been associated with a reduced risk of obesity, urinary tract infections, chronic kidney disease, cardiovascular disease, and a reduction in the incidence of hyperglycemia [5][6][7][8][9][10][11]. Despite these benefits, recent cross-sectional surveys have shown that 60% of men and 40% of women do not comply with the EFSA recommendations for daily water intake [12], which may alter the long-term health risk profile in persons who habitually consume low volumes of water on a daily basis [13,14]. Although 40% of women were found to not meet current EFSA standards, they were more than twice as likely to meet the adequate intake standards for daily fluid intake than that of men [12].…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining adequate hydration is essential to optimal health [ 1 , 2 , 3 ] and athletic performance [ 4 , 5 ]. Dehydration can contribute to a host of issues, including altered cognition and digestion, as well as organ dysfunction in the heart, kidneys, and skin [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, practical and accurate individualized recommendations for water consumption levels remain enigmatic. Instead, monitoring of urine color according to a standardized color scale has been demonstrated to detect an elevated urine osmolality in free-living individuals, and has been suggested to be a sufficient monitoring of hydration status for the general population, 31 which may be a useful, low burden technique in individuals with migraine.…”
Section: Favorable Risk: Benefit Analysis-omega-3:omega-6mentioning
confidence: 99%